2023
DOI: 10.3390/su15032469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social and Economic Factors on Construction Project Performance in Pakistan

Abstract: The performance of a building project is a key determinant of its ultimate success. The failure of a construction project can be attributed to a variety of issues. Among these criteria, success and long-term sustainability have been identified as crucial. It has been established that social and economic considerations play a considerable effect in project completion. In Pakistani construction projects, however, there is a lack of a systematic framework for measuring the impact of social and economic elements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Multiple regression analysis is a statistical method used to examine the relationship between one dependent variable and two or more independent variables. It is used to predict the value of a dependent variable based on the values of one or more independent variables [56]. The relationship is modeled through a linear equation that estimates the relationship between the variables.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple regression analysis is a statistical method used to examine the relationship between one dependent variable and two or more independent variables. It is used to predict the value of a dependent variable based on the values of one or more independent variables [56]. The relationship is modeled through a linear equation that estimates the relationship between the variables.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, poverty was a contributing factor to stalling of projects. The study identified key challenges facing construction in the developing world (Khahro et al, 2023). Mavetera (2019) conducted a study to assess the impact of socio-economic factors on the construction sector in South Africa.…”
Section: Effect Of Political Factors On Completion Of Construction Pr...mentioning
confidence: 99%
“…The building of hospitals and schools is essentially a community led need (Bucăţa & Rizescu, 2019). Khahro et al (2023) illustrated that lack of skilled labor and resources were key social factors having an impact on construction completion in Pakistan. Moreover, poverty was a contributing factor to stalling of projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are eight main aspects of performance in hydropower development projects, including safety, quality, health, environmental protection, schedule, problem solving, cost, and migration [41,42]. The process of innovation, alongside the emanating novelties, significantly influences project performance, serving as critical determinants of project quality and organizational efficacy [43,44].…”
Section: Project Performancementioning
confidence: 99%